Cranioplasty: Using 3D Implants for Skull Defect Cranioplasty (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Currently, the implementation of the principles of minimally invasive microneurosurgery, the use of modern neuroimaging methods, and comprehensive adequate neuroreanimation intensive care have reduced mortality in severe traumatic brain injuries and brain tumors, but have not reduced the number of patients with post-trepanation skull defects. Despite a long history of study, the problem of choosing a method for restoring the integrity of the skull after resection trepanations and the removal of space-occupying lesions affecting the bones of the vault and base of the skull remains relevant [1]. A violation of the skull's hermeticity leads to the formation of a new pathological condition - "trepanned skull syndrome." The inability of a post-trepanation defect to spontaneously restore bone tissue, as well as functional and organic disorders that arise in patients, serve as reasons for cranioplasty [2,3].